Sera from patients with sepsis induce nitric oxide production in vascular smooth muscle cells - Hiroshi Fujita; Junji Tomiyama; Hideki Kudo; Ikuo Morita; Sei-itsu Murota (Hindawi Limited, 2000)
Background: Nitric oxide (NO) is an important physiological mediator of vascular tone and is involved in pathophysiology of septic shock. Although plasma nitrite is a stable end product of NO oxidation derived from endogenous NO, the plasma nitrite level is also easily affected by the intake of various foods, bacterial products and renal functional status.